Captive of the Labyrinth : Sarah L. Winchester, Heiress to the Rifle Fortune, Revised and Updated Edition - Ignoffo, Mary Jo, 1955- (Book collections on Project MUSE., 2022)
"Captive of the Labyrinth is reissued here to commemorate the 100th anniversary of the death of rifle heiress Sarah L. Winchester in 1922. Mary Jo Ignoffo demystifies the life of Sarah L. Winchester (1839-1922) who, for too long has existed as a ghost herself-a woman whose existence lies somewhere between the facts of her life and a set of sensationalized news stories. When Winchester's home was purchased after her death, it was transformed into a tourist attraction as a haunted house. The bizarre, sprawling mansion and the enigmatic nature of Winchester's life were exaggerated by the new owners to generate publicity for their business. But as the mansion has become more widely known, the person of Winchester has receded further from reality"--